PENGEMBANGAN MODUL SEJARAH LOKAL KOTA METRO UNTUK MENGUATKAN KESADARAN SEJARAH - Fadhilah Syahidah; Elis Setiawati (Swarnadwipa, 2018)
The objectives of this research are (1) to describe the local history teaching materials used in SMA N 1 Metro, (2) get a general description of the level of awareness of history of SMA N 1 Metro students, (3) get the module design of local history of Metro City to strengthen the awareness of history, (4) to describe the opinion of experts and practitioners about the feasibility of local Metro City's local history module in strengthening historical awareness. The method used in this research is research and development with the development model adapted from Sugiyono level 1, that is research to produce the product but not test it. The study results are (1) the use of learning resources in SMA N 1 Metro is still synonymous with textbooks or print and the internet, (2) the level of awareness of high school students N 1 Metro by 67% with high category, (3) module of local history City Metro is designed in accordance with the syllabus of the 2013 curriculum entitled 'History and Development of Metro City', (4) the result of material validation of phase one with percentage of 73% and stage two of 89%, an increase of 16%. The results of the design validation stage one 61%, after the improvement and validation test conducted in phase two to 89%, with a 28% increase. Based on the results of the validation, the local delivery module Metro City to strengthen the consciousness declared feasible test.